Technological sequence of creating components of the training system of the future officers to the management of physical training - Olkhovy O.M (Kharkov National Pedagogical University, 2012)
The goal is to determine constructive ways of sequence of constructing components of the training system of the future officers to carry out official questions of managing the physical training in the process of the further military career. The structural logic circuit of the interconnections stages of optimum cycle management and technological sequence of constructing the components of the training system of the future officers to the management of physical training, which provides: definition of requirements to the typical problems of professional activities on the issues of the leadership, organization and conducting of physical training, the creation of the phased system model cadets training, training of the curriculum discipline "Physical education, special physical training and sport"; model creation and definition of criteria of the integral evaluation of the readiness of the future officers to the management of physical training was determined through the analysis more than thirty documentary and scientific literature.